2012
DOI: 10.1007/s11832-012-0451-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Dega acetabuloplasty and Salter innominate osteotomy on acetabular remodeling monitored by the acetabular index in walking DDH patients between 2 and 6 years of age: Short- to middle-term follow-up

Abstract: Introduction The surgical management of neglected developmental dysplasia of the hip (DDH) in walking children has always been a challenge to orthopedic surgeons. The aim of this study was to evaluate the short-to middle-term clinical and radiographic results of the management of DDH. Patients and methods Patients less than 6 years old using two of the most commonly used osteotomies, namely, Salter innominate osteotomy and the Dega acetabuloplasty. Special attention was paid to acetabular remodeling after conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 18 publications
6
54
2
6
Order By: Relevance
“…El-Sayed and colleagues 99 reported a series of 109 hips, 61 of which underwent an SIO and 48 of which underwent a Dega acetabuloplasty based on the treating surgeon's preference. The worst outcome was seen in the group less than 4 years of age treated by Dega osteotomy, and this was attributed to the more technically demanding procedure of the smaller ilium.…”
Section: Pelvic Osteotomiesmentioning
confidence: 99%
“…El-Sayed and colleagues 99 reported a series of 109 hips, 61 of which underwent an SIO and 48 of which underwent a Dega acetabuloplasty based on the treating surgeon's preference. The worst outcome was seen in the group less than 4 years of age treated by Dega osteotomy, and this was attributed to the more technically demanding procedure of the smaller ilium.…”
Section: Pelvic Osteotomiesmentioning
confidence: 99%
“…If the lateralisation is >40 % or the hip is dislocated, a bony reconstruction is necessary, and in recent years combining reconstruction with soft-tissue procedures has become the standard treatment to improve function. Reconstruction of the acetabulum using the technique of Dega stabilises the pelvis better than the techniques described by Chiari or Salter because it is a stable and incomplete osteotomy [15] and the medial corticalis of the os ilium is not affected.…”
Section: Introductionmentioning
confidence: 99%
“…Barrett et al [16] stated that in the 7-year followup of 4 different groups undergoing Salter osteotomy, they reduced the acetabular index by an average of 16 degrees. El-Sayed et al [17] reported that they achieved 18-19-degree corrections in two different groups under and over 4 years of age using Salter osteotomy. In a study by Ahmed Essam et al [18] it was stated that they reduced the preoperative mean acetabular index from 47.8 degrees to 26.7 degrees after Salter osteotomy in patients with DDH.…”
Section: Discussionmentioning
confidence: 99%